2021
DOI: 10.7554/elife.62825
|View full text |Cite
|
Sign up to set email alerts
|

Response-based outcome predictions and confidence regulate feedback processing and learning

Abstract: Influential theories emphasize the importance of predictions in learning: we learn from feedback to the extent that it is surprising, and thus conveys new information. Here, we explore the hypothesis that surprise depends not only on comparing current events to past experience, but also on online evaluation of performance via internal monitoring. Specifically, we propose that people leverage insights from response-based performance monitoring – outcome predictions and confidence – to control learning from feed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 102 publications
5
28
0
Order By: Relevance
“…Jocham et al (2014)) converge on a common integrative process reflected in a centroparietal positivity. In line with previous research (Chase et al, 2011;Fromer et al, 2021;Nassar et al, 2019;Ullsperger, Fischer, et al, 2014;Wessel & Aron, 2017) we suggest, that this EEG correlate reflects a final pathway of adaptation that sets the stage for future behaviour. This view is supported by our decoding analyses suggesting that behaviour switches are best predicted by an EEG activity with a topography and latency matching the P3b.…”
Section: A Common Late Centroparietal Positivity Serves As a Final Pathway Of Adaptation That Guides Future Behavioursupporting
confidence: 92%
“…Jocham et al (2014)) converge on a common integrative process reflected in a centroparietal positivity. In line with previous research (Chase et al, 2011;Fromer et al, 2021;Nassar et al, 2019;Ullsperger, Fischer, et al, 2014;Wessel & Aron, 2017) we suggest, that this EEG correlate reflects a final pathway of adaptation that sets the stage for future behaviour. This view is supported by our decoding analyses suggesting that behaviour switches are best predicted by an EEG activity with a topography and latency matching the P3b.…”
Section: A Common Late Centroparietal Positivity Serves As a Final Pathway Of Adaptation That Guides Future Behavioursupporting
confidence: 92%
“…Our efficacy-updating results are a reminder that many aspects of feedback are reflected in prediction error signals (Langdon et al 2018; Frömer et al 2021b). In the present study, we intentionally separated feedback about reward and efficacy to isolate the cognitive and neural learning mechanisms associated with each.…”
Section: Discussionmentioning
confidence: 80%
“…To visualize the topographies of the relevant ERP effects, we fitted the relevant models to all 64 channels and then plotted the posterior estimates of the effects of interest at each electrode (cf. Frömer et al, 2021b).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The authors suggest that confidence approximates the amount of noise in the efference copy signals (i.e., their precision), which together with the efference copy and feedback, allow the individuals to make inferences about the success of their action. Their results showed that participants with more accurately "calibrated" confidence (i.e., more accurate estimate of noise in efference copies) learned better (Frömer et al, 2021). This suggests that LSW could reflect higher-order monitoring mechanisms: Whereas SIS in the N1 time-window may reflect automatic "online" corrections based on the efference copy (Hickok et al, 2011;Houde & Nagarajan, 2011;Tourville & Guenther, 2011), the LSW could reflect monitoring processes that integrate multiple sources of information (e.g., perceived auditory feedback on one's pronunciation, predictions based on the efference copy, and the individual's confidence in the accuracy of these predictions).…”
Section: Discussionmentioning
confidence: 99%